Hematopoietic stem cell transplantation for children with acute myeloid leukemia in second remission: A report from the Australasian Bone Marrow Transplant Recipient Registry and the Australian and New Zealand Children's Haematology Oncology Group. Issue 8 (20th May 2019) - Selim, Adrian; Alvaro, Frank; Cole, Catherine H.; Fraser, Chris J.; Mechinaud, Francoise; O'Brien, Tracey A.; Shaw, Peter J.; Tapp, Heather; Teague, Lochie; Nivison‐Smith, Ian; Moore, Andrew S.
Abstract: Background: Approximately one‐third of children with acute myeloid leukemia (AML) relapse, requiring re‐treatment and allogeneic hematopoietic stem cell transplantation (HSCT). Although achieving second complete remission (CR2) prior to HSCT is desirable, once CR2 is attained, it is unclear if there is any benefit from further chemotherapy prior to HSCT. Moreover, although pre‐HSCT minimal residual disease (MRD) has prognostic value in acute lymphoblastic leukemia, the benefit of MRD reduction after achieving CR prior to HSCT is less clear for AML. Procedure: To address these questions, we analyzed data from pediatric transplant centers in Australia and New Zealand concerning relapsed childhood AML cases occurring between 1998 and 2013. Given the retrospective nature of our analysis and assay data available, we analyzed patients on the basis of measurable residual disease (MeRD) by any methodology, rather than MRD in the conventional sense. Results: We observed improved overall survival (OS) in children receiving two chemotherapy cycles, compared to one cycle or three or more cycles pre‐HSCT. Improved OS with two cycles remained significant for patients without MeRD after cycle 1. Conclusions: These data suggest that a second chemotherapy cycle pre‐HSCT may improve survival by lowering disease burden. Prospective trials assessing strategies to reduce pre‐HSCT MRD in relapsed childhood AML are warranted.